TINGKAT KECUKUPAN ENERGI PROTEIN PADA IBU HAMIL TRIMESTER PERTAMA DAN KEJADIAN KEKURANGAN ENERGI KRONIS - Anisatun Azizah; Merryana Adriani (Universitas Airlangga, 2017)
Chronic Energy Deficiency (CED) cases are still occur in Indonesia, mainly due the imbalance of nutrients intake and it can lead to the growth retardation, either physical or mental. The most important period of the gestational age is atthe first trimester because the formation of various vital organs of the fetus occurs. The purpose of this research was to analyze the relationship between energy and protein adequacy level with the occurance of CED in the first trimester of pregnant women. This research was an observational analytic study with cross sectional design. The number of sample taken was 22 people which randomly selected. The data was analyzed using chi square and fisher exact test (α = 0,05). The results showed that there were 50% of pregnant women having Chronic Energy Deficiency and 50% did not have Chronic Energy Deficiency. Based on cross-tabulation, pregnant women who have low protein adequacy level have a similar CED prevalence with good protein adequacy level. There was no relationship between carbohydrate (p = 1,000), protein (p = 1,000), and fat (p = 0,635) adequacy level with CED in pregnant women (p > 0,05).